2018
DOI: 10.1111/ipd.12363
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic efficacy of articaine versus lidocaine in children's dentistry: a systematic review and meta‐analysis

Abstract: There is low quality evidence suggesting that both articaine as infiltration and lidocaine IAD nerve blocks presented the same efficacy when used for routine dental treatments, with no difference between patient self-reported pain between articaine and lidocaine during treatment procedures. Yet, significantly less pain post-procedure was reported following articaine injections. There was no difference in the occurrence of adverse events between articaine and lidocaine injections following treatment in paediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…11 A subsequent 2018 study found that there is no difference between articaine and lidocaine in frequencies of anaesthetic-related adverse events in children. 83 Adverse effects. Paraesthesia associated with dental anaesthesia is defined as numbness or tingling of the mouth and face.…”
Section: Overview Of Previous Systematic Reviewsmentioning
confidence: 99%
“…11 A subsequent 2018 study found that there is no difference between articaine and lidocaine in frequencies of anaesthetic-related adverse events in children. 83 Adverse effects. Paraesthesia associated with dental anaesthesia is defined as numbness or tingling of the mouth and face.…”
Section: Overview Of Previous Systematic Reviewsmentioning
confidence: 99%
“…performed a meta-analysis and reported significant discrepancies in the expression of results as well as a high risk of bias in children's studies. More accurate methodologies, including better standardization of reporting outcomes that provide less heterogeneous data for meta-analysis, are needed [12]. Tirupathi et al…”
Section: Introductionmentioning
confidence: 99%
“…The use of articaine has also received attention in pediatric dentistry, albeit in a limited manner. In a systematic review and meta-analysis of six studies, Tong et al ( 7 ) have suggested equal efficacy of articaine and lignocaine for pediatric dental procedures. Contrastingly, in another recent review, Taneja et al ( 8 ) have indicated that articaine may have better efficacy as compared to lignocaine in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%